Corrección quirúrgica de infarto de intestino delgado en un equino mediante yeyunocecostomía con grapadora quirúrgica mecánica - Duque B., Diego L.; Coral D., Elizabeth; Bran, José (Revista Colombiana de Ciencias Pecuarias, 2016)
Summary A 7- years-old criollo colombiano stallion was referred to the Large Animal Hospital Centro de Veterinaria y Zootecnia CES (Envigado, Colombia) because of an acute abdominal syndrome that had persisted for seven hours despite medical treatment. On physical examination the stallion was depressed, dehydrated (6%), borborygmi were diminished, rectal temperature was 37.1 °C 37.1 °C, hearth and respiration rates , hearth and respiration rates hearth and respiration rates were 40 beats/min and 28 breaths/min, respectively. On rectal examination and abdominal ultrasonography small intestine was distended. Peritoneal fluid analysis was altered. Signs of pain were nonresponsive to analgesics. The diagnosis by exploratory laparotom laparotomy was infarction of small intestine (seven meters of the y was infarction of small intestine (seven meters of the was infarction of small intestine (seven meters of the infarction of small intestine (seven meters of the of small intestine (seven meters of the jejunum and proximal portion of the ileum) of unknown etiology. A jejunocecostomy was done using a GIA etiology. A jejunocecostomy was done using a GIA . A jejunocecostomy was done using a GIA 80 surgical stapler (United Surgical). Postsurgical recuperation was successful. This case becomes the first report of a jejunocecostomy in a horse in Colombia.